T cell receptor grafting allows virological control of hepatitis B virus infection - Wisskirchen, Karin; Kah, Janine; Malo, Antje; Asen, Theresa; Volz, Tassilo; Allweiss, Lena; Wettengel, Jochen M.; Luetgehetmann, Marc; Urban, Stephan; Bauer, Tanja; Dandri-Petersen, Maura; Protzer-Knolle, Ulrike (The journal of clinical investigation, 2019)
T cell therapy is a promising means to treat chronic hepatitis B virus (HBV) infection and HBV-associated hepatocellular carcinoma. T cells engineered to express an HBV-specific T cell receptor (TCR) may cure an HBV infection upon adoptive transfer. We investigated the therapeutic potential and safety of T cells stably expressing high-affinity HBV envelope- or core-specific TCRs recognizing European and Asian HLA-A2 subtypes. Both CD8(+) and CD4(+) T cells from healthy donors and patients with chronic hepatitis B became polyfunctional effector cells when grafted with HBV-specific TCRs and eliminated HBV from infected HepG2-NTCP cell cultures. A single transfer of TCR-grafted T cells into HBV-infected, humanized mice controlled HBV infection, and virological markers declined by 4 to 5 log or below the detection limit. Engineered T cells specifically cleared infected hepatocytes without damaging noninfected cells when, as in a typical clinical setting, only a minority of hepatocytes were infected. Cell death was compensated by hepatocyte proliferation, and alanine amino transferase levels peaking between days 5 and 7 normalized again thereafter. Cotreatment with the entry inhibitor myrcludex B ensured long-term control of HBV infection. Thus, T cells stably transduced with highly functional TCRs have the potential to mediate clearance of HBV-infected cells, causing limited liver injury.
Gesehen am 20.08.2019